The trypanocidal activity of the alkaloid oliverine involves inhibition of DNA synthesis - Garro, H. A.; Juri Ayub, M.; Nieto, M.; Lucero Estrada, C.; Pungitore, C. R.; Tonn, C. E. (Cellular and Molecular Biology, 2010)
The Trypanosoma cruzi parasite is an etiologic agent of the American trypanosomiasis called Chagas disease. This pathology affects more than 24 million persons and represents one of the most important public health problems in Latin America. Taking into account this, it is necessary the search of new antitrypanosomal agents that show a major level of efficacy and minor indexes of toxicity in affected patients. Vast source of them are the natural products from plants with enormous structural diversity. A particular type of these compounds is represented by aporphinoid alkaloids. In our experiments, anonaine (2), oliverine (3) and guatterine (5) displayed antitrypanosomal activity. The compound 3 showed the most important activity with an IC50 = 12.00 ± 0.36 Î¼M. Its mechanism of action may include inhibition of DNA synthesis.